PENGEMBANGAN MEDIA VIDEO PEMBELAJARAN MATEMATIKA PADA MATERI TEOREMA PHYTAGORAS DI SMPN 05 METRO - Essa Yosinta; Satrio Wicaksono Sudarman; Rina Agustina (EMTEKA: Jurnal Pendidikan Matematika, 2024)
This research aims to determine the increase in students' mathematics learning outcomes through a project based learning in Statistics of Class VIII-A of SMP Negeri 29 Samarinda at 2021/2022. The research method applied was classroom action research with 28 students as research subjects. A total of 22 students were analyzed because 6 students did not participate in full learning. Data collection techniques used documents in the form of basic scores (student UTS scores), individual assignments (Individual LKS), group assignments (Group LKS), Project Progress Tables, Activity Observation Sheets (Students and Teachers), and End of Cycle Tests. The results of students' mathematics learning were seen from the increase in the average value of student learning outcomes from basic values to cycle I, namely 48.64 to 63.74. In cycle II the average value increased to 72.76. In cycle III the average value increased to 85.04. The activities of teachers and students in learning in cycle I were still classified as sufficient and very insufficient. In cycle II, teacher and student activities reached the good and sufficient categories. In cycle III there had been an increase and achieved very good results for teacher and student activities. The project was successfully completed as a group according to the LKS guidelines with an average final assignment score of 85.99. The project based learning model was successfully implemented and can improve student learning outcomes in statistics of class VIII-A of SMP Negeri 29 Samarinda at 2021/2022.